Peran Tokoh Islam dalam Menumbuhkan Nilai-Nilai Moderasi Melalui Praktik Ekonomi di Madura - Rosyidi, Mohammad; Harisah, Harisah; Al Humaidy, Mohammad Ali (Universitas Islam Lamongan, 2024)
This study aims to see the role of religious figures through pesantren engaged in the economic sector. As an educational institution, pesantren have penetrated into various scientific fields, both in theory and practice, including in the field of economics. Pesantren led by a kiai in Madura have a very important role to be used as icons for the community in acting and behaving in everyday life. In economic practice, Islamic figures have been massively entrepreneurial to foster business awareness in their respective pesantren. Through this application, the economy in pesantren can grow independently in terms of funding to support the needs of their institutions. This study is a qualitative indicator with a sample approach in the form of library research (library research) collecting information in the form of books, journals, interviews, articles, news available in online media. The findings show that pesantren in Madura through economic activities have a wide reach in providing moderate understandings because Madura itself is a heterogeneous area. So that there is no discrimination against economic actors who are not the same in background as the general public in Madura. the application of moderation through real economic practices exists in Madura, because in terms of values, the key to moderation has been implemented in practice, especially in pesantren led by Islamic figures.